المشاكل التي يواجهها الطلاب في تعلم مهارة الاستماع في اللغة العربية :‏ ‏دراسة حالية بالكلية الجامعة الإسلامية العالمية سلانجور /‏ - موسى، محمد الأول (Ma'had al-Tarbiyah, al-Jami'ah al-Islamiyah al-'Alamiyah Malizya, 2008)
The study investigates the problems faced by the students in acquiring Arabic language listening skill from the Arabic Language Department at International Islamic University College Selangor. The study discusses the problems of acquiring Arabic language listening skills, the causes as well as possible solution to them. The researcher has selected 201 students conveniently for his study for three consecutive years' students from department of Arabic language for data collection. The data have been analyzed by using SPSS program package version 11.5. The analysis was based on descriptive; frequency distribution, frequency table, and percentage to find out the result of the problems. Finally the study ascertained that the students faced lot problems in relation to learning Arabic language listening skill. In addition, it was revealed to students the solutions to the problems and gives some suggestion on how to tackle those problems.